MODIFICATIONS ENCOUNTERED IN THE BLOOD AND MARROW COUNTS OF GUINEA PIGS TREATED WITH SUBLETHAL DOSES OF ANTIRETICULAR CYTOTOXIC SERUM - VALDES ORNELAS, OSCAR; S K, GRABERT (Universidad Nacional Autónoma de Mexico, Instituto de Biología, CD MEXICO, DF, MEX, 1948)
It is intimated that antibodies sensitize or denature the bacteria and allow the action of the complement-lysozyme system The presence of lysozyme in man and animal tissues and body fluids is possibly related with other enzymes, and the antibody-compleme
REV SOC MEX HIST NAT
Keywords: MODIFICATIONS ENCOUNTERED, BLOOD, MARROW COUNTS, GUINEA PIGS, SUBLETHAL DOSES, ANTIRETICULAR CVTOTOXIC SERUM; CIENCIAS DE LA VIDA